Preparation and Characterization of Potato Starch-Based Bioplastic for Food Packaging Applications - Lim, You Chen; Lee Woon Kiow; Norfazillah Talib (Research Progress in Mechanical and Manufacturing Engineering, 2025)
The hazardous impact of fossil fuel-based plastics on the environment and society has drawn attention toward alternative sources. Bioplastics are a type of renewable resource that can be degraded by microorganisms and prevent chemical leaching. So, the starch-based bioplastics properties became an important factor to replace fossil fuel-based plastics. This study aims to characterize the addition of both Zinc Oxide and Chitosan to potato starch bioplastics films. Bioplastic potato starch-based films were prepared by using the casting method. The concentration of zinc oxide in the bioplastics samples varies from 1.0 %, 2.0%, and 3.0% (w/w) by weight of starch. Also, the chitosan content in the bioplastic varies from 4.0%, 6.0%, and 8.0% (w/w) by weight of starch. The result of the SEM samples shows that the surface becomes smoother as the zinc oxide and chitosan content is higher. Sample 3 shows the lowest crystallinity value, which is 74%, determined by X-ray diffraction analysis (XRD), indicating a high degree of degradation. Samples 7 and 9 had 79% crystallinity value, which is the highest, which is represented by better mechanical properties and longer shelf life. The FTIR data show the IR spectra presented the existence of O-H groups, C-H groups, C=C groups and C-O-C ester groups. The change of group functions was analysed, and no changes occurred. So, there was only physical interaction in the bioplastic samples.